Pregnancy and the Plastic Surgery Resident. Issue 1 (January 2017) - Garza, Rebecca M.; Weston, Jane S.; Furnas, Heather J.
Abstract : Background: Combining pregnancy with plastic surgery residency has historically been difficult. Two decades ago, 36 percent of plastic surgery program directors surveyed actively discouraged pregnancy among residents, and 33 percent of women plastic surgeons suffered from infertility.1 Most alarmingly, 26 percent of plastic surgery trainees had had an elective abortion during residency. With increasing numbers of women training in plastic surgery, this historical lack of support for pregnancy deserves further attention. Methods: To explore the current accommodations made for the pregnant plastic surgery resident, an electronic survey was sent to 88 plastic surgery program directors in the United States. Results: Fifty-four responded, for a response rate of 61.36 percent. On average, a director trained a total of 7.91 women among 17.28 residents trained over 8.19 years. Of the women residents, 1.43 were pregnant during a director's tenure, with 1.35 of those residents taking maternity leave. An average 1.75 male residents took paternity leave. Approximately one-third of programs had a formal maternity/paternity leave policy (36.54 percent) which, in most cases, was limited to defining allowed weeks of leave, time required to fulfill program requirements, and remuneration during leave. Conclusions: This survey of plastic surgery directors is a first step in defining the challenges training programs face in supporting the pregnant resident. Directors provided comments describing their challenges accommodating an absent resident in a small program and complying with the American Board of Plastic Surgery's required weeks of training per year. A discussion of these challenges is followed by suggested solutions.